2021
DOI: 10.1007/s00198-021-05911-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of fracture liaison services on subsequent fractures and mortality: a systematic literature review and meta-analysis

Abstract: This systematic review and meta-analysis suggests that fracture liaison service (FLS) is associated with a significantly lower probability of subsequent fractures and mortality although the latter was only found in studies comparing outcomes before and after the introduction of an FLS. Introduction To systematically review and evaluate the impact of fracture liaison services (FLSs) on subsequent fractures and mortality using meta-analysis. Methods A literature search was performed within PubMed and Embase to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 40 publications
(120 reference statements)
4
41
0
1
Order By: Relevance
“…Furthermore, hip fracture patient survival is related with the presence of comorbidities at 2 years of follow-up [ 13 ]. A recent systematic review and meta-analysis conducted on Fracture Liaison Services demonstrated a lower probability or subsequent fractures and mortality [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hip fracture patient survival is related with the presence of comorbidities at 2 years of follow-up [ 13 ]. A recent systematic review and meta-analysis conducted on Fracture Liaison Services demonstrated a lower probability or subsequent fractures and mortality [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“… 53 It is now clear that high-intensity FLS (which comprise identification, investigation, and initiation of therapy) have been successful in reducing the incidence of new fractures. 54 Moreover, cost-effectiveness analyses of FLS showed gains in quality-adjusted life years (QALY) for expenses below the willingness to pay thresholds. 55 A recently published meta-analysis showed that the implementation of FLS is associated with lower probability of subsequent fractures with a trend toward mortality reduction.…”
Section: Fracture Liaison Servicesmentioning
confidence: 99%
“… 55 A recently published meta-analysis showed that the implementation of FLS is associated with lower probability of subsequent fractures with a trend toward mortality reduction. 54 Evidence mostly came from indirect comparisons between hospitals with and without FLS and from the comparison between pre-FLS versus post-FLS periods in the same hospital. Majumdar et al 56 in 2018 conducted a pragmatic randomized controlled trial comparing two different FLS strategies.…”
Section: Fracture Liaison Servicesmentioning
confidence: 99%
“…8,9 Se ha reportado internacionalmente una tasa de fractura subsecuente de 7.7% posterior a la implementación del modelo FLS comparado con la tasa de 10.9% previo a su establecimiento. 10 En algunos estudios disminuye hasta 5% la presentación de fractura subsecuente en un periodo de cinco años después de presentar la fractura inicial. 11 Una fractura previa es un fuerte predictor de fractura posterior; sin embargo, las tasas de tratamiento postfractura son bajas.…”
Section: Wwwmedigraphicorgmx Introducciónunclassified